2020
DOI: 10.1080/17512786.2020.1805794
|View full text |Cite
|
Sign up to set email alerts
|

Headline Format Influences Evaluation of, but Not Engagement with, Environmental News

Abstract: Sparked by a collaboration between academic researchers and science media professionals, this study sought to test three commonly used headline formats that vary based on whether (and, if so, how) important information is left out of a headline to encourage participants to read the corresponding article; these formats are traditionally-formatted headlines, forward-referencing headlines, and question-based headlines. Although headline format did not influence story selection or engagement, it did influence part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 45 publications
4
13
0
Order By: Relevance
“…Supporting our prior work suggesting that our science curiosity scale (Kahan et al, 2017) predicts engagement with science media (e.g., Janét et al, 2020), logistic regression analyses show that science curiosity was positively associated with listing at least one science video (b = 0.59, exp(b) = 1.81, 95% CI[1.28, 2.60], p < 0.001) and at least one technology video (b = 0.53, exp(b) = 1.70, 95% CI[1.21,2.41], p = 0.002). Notably, it was Women Seem More Likely to Access Science Videos for Information Gathering; Men Access Science Videos for Both Information Gathering and Entertainment…”
Section: Men Are More Likely To Have a Technology Video In Their Watch Historysupporting
confidence: 83%
See 1 more Smart Citation
“…Supporting our prior work suggesting that our science curiosity scale (Kahan et al, 2017) predicts engagement with science media (e.g., Janét et al, 2020), logistic regression analyses show that science curiosity was positively associated with listing at least one science video (b = 0.59, exp(b) = 1.81, 95% CI[1.28, 2.60], p < 0.001) and at least one technology video (b = 0.53, exp(b) = 1.70, 95% CI[1.21,2.41], p = 0.002). Notably, it was Women Seem More Likely to Access Science Videos for Information Gathering; Men Access Science Videos for Both Information Gathering and Entertainment…”
Section: Men Are More Likely To Have a Technology Video In Their Watch Historysupporting
confidence: 83%
“…To determine whom is interested in engaging with science content, my collaborators and I developed the "Science Curiosity Scale" (see also Kahan et al, 2017;Motta et al, 2019). Individuals' science curiosity scores are strongly predictive of their engagement with educational science video (Kahan et al, 2017) as well as other types of science media (Janét et al, 2020). In my collaborative research with KQED Science, we have found that in some cases, women were less likely than equally science curious men to agree to watch an educational science video (Kahan, 2019).…”
Section: Media Producers Report Gender Disparities In Digital Video Usementioning
confidence: 99%
“…This method adapted a previously created survey by Janét, Richards & Landrum (2022) to measure participant perception of the credibility of social media posts. The survey consists of ten items, answered with a six-point Likert-type scale ranging from 1 (disagree) to 6 (strongly agree).…”
Section: Methodsmentioning
confidence: 99%
“…Another line of research is investigating how headlines used in social media posts affect user perceptions. In that vein, Janét, Richards & Landrum (2022) investigated three types of headlines about environmental topics: traditional ones (with straightforward information), those that ask questions, and forward-referencing headlines (‘You’ll never believe what…’). They found that headlines did not affect story engagement or selection but did affect credibility, and the question-formatted headlines seemed the least credible.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation